Reaction plane correlated triangular flow in Au + Au collisions at √ s N N = 3 GeV - STAR Collaboration (Physical Review C, 2024)
We measure triangular flow relative to the reaction plane at 3 GeV center-of-mass energy in Au+Au collisions at the BNL Relativistic Heavy Ion Collider. A significant v3 signal for protons is observed, which increases for higher rapidity, higher transverse momentum, and more peripheral collisions. The triangular flow is essentially rapidity-odd with a slope at midrapidity, dv3/dy|(y=0), opposite in sign compared to the slope for directed flow. No significant v3 signal is observed for charged pions and kaons. Comparisons with models suggest that a mean field potential is required to describe these results, and that the triangular shape of the participant nucleons is the result of stopping and nuclear geometry.
Keywords: dept.phy; peer-reviewed